The [unk]-Neumann Problem on (Weakly) Pseudo-Convex Two-Dimensional Manifolds - Kohn, J. J. (1972)
When the Levi-form vanishes at boundary points of a pseudo-convex manifold, more delicate invariants are required to describe the function theoretic properties of the manifold. These are introduced here; the proof of the main theorem and other results, which will be described in more detail elsewhere, are described.